Public value and quality factors for continuous usage of police M-government services among users - Alkaabi, Saqr Khalfan Ali (2022)
Government of the UAE has adopted M-government as one of the ways to transform their cities to smart cities. In this case, the continuous usage of the M-government services is considered crucial for the sustainability of smart cities. Recognizing the importance of quality factors and value of public services that are provided through M-government services, this study aims to investigate the relationship of quality factors and public value of M-government services on the continuous usage of M-government. Thus far, there has been a minimal study of the relationship between public value and continuous use of M-government services. Adopting two theories, namely the Information System Success Factors (IS) theory and Public Value theory, this study hypothesized the direct relationship of the quality factors and public value, and the mediating relationship of two variables, namely trust and satisfaction with the continuous intention to use M-government services. To test and validate these relationships, a quantitative survey research has been adopted, in which data were collected from the users of M-police services. A simple random sampling technique was used for determining the sample and data from 379 respondents were analysed for multivariate analysis, confirmatory factor analysis, reliability analysis of the constructs and structural equation modelling. This study found public value and quality factors have significant positive relationship with continuous usage and trust of m-police services, while public value did not have significant relationship with trust, and satisfaction did not have significant relationship with continuous usage of m-government. With respect the effect of trust and satisfaction as mediators, both partially mediate the relationship between quality factors and continuous usage, and between public value and continuous usage of M-government services. Although this study focuses on the use of m-police services, it can be generalized to other usage of M-government services provided by other government bodies. Further, the examination of M-government services as public value is relevant considering that M-government services are used by all citizens. Hence, the findings of this study are valuable for theoretical and practical knowledge. It is also valuable for the government, particularly the UAE to consider the factors that contribute to satisfaction, trust and continuous usage of M-government that contributes to the sustainability of their smart cities.